P56-F Auditory-motor task triggers gamma and beta oscillations in patients with schizophrenia and auditory verbal hallucinations. Issue 7 (July 2019) - Ívarsson, Eysteinn; Banea, Ovidiu C.; Magnúsdóttir, Brynja B.; Jónasson, Aron D.; Gargiulo, Paolo; Haraldsson, Magnús; Wassermann, Eric; Stefánsson, Sigurjón
Abstract : Background: In a study with intracranial recordings, auditory-verbal stimuli elicited augmented gamma-oscillations in the posterior portion of the superior temporal gyrus, whereas hand-motor responses elicited gamma-augmentation in the pre- and postcentral gyri (Nagasawa et al., 2010). We aimed to investigate if motor cortical activation (MCA) during an auditory-motor (AM) task is affected by laterality of hand motor responses in healthy subjects (HS) and in patients with auditory verbal hallucinations (AVH). Methods: Eight HS and ten patients were asked to press a button using the thumb of both hands independently, during two sessions of 3 min. Each session contained 40 trials; 20 auditory-verbal commands saying "Press" and 20 commands saying "Do not press" (Nagasawa et al., 2010). MCA analysis epochs had duration of 500 ms following the button "press". We used high-density 256 EEG ANT Neuro. Here we show preliminary results of MCA in HS and AVH patients using power spectral density (PSD) and topographical frequency maps including both hands sensory-motor regions. Results: The preliminary data show that the laterality of the cortical activation related to the AM task may not be affected to a large degree by the motor reaction. Resting state EEG and AM task brain maps showed fragmented EEG topography in patients with schizophrenia for all analyzed band frequencies. Conclusions: With this method we were able to trigger high beta and gamma bands activity in regions related to sensory-motor cortex. The topography of these frequencies remained stable when the participant used the right or the left hand.